THE ROLE OF TOURISM ASSISTANTS IN IMPROVING TOURISM STATISTICS - Jumayev Akbar Mahmudovich (American Journals, 2025)
Tourism has become one of the fastest growing competitive sectors in the world economy. The number of tourists at the international level has reached 1.8 billion. people. Tourism revenues have reached 1.7 trillion US dollars, accounting for 7% of world exports and 29% of services exports. Tourism revenues in world exports rank third after the chemical industry and fuel and energy exports. Tourism occupies a key place in the leading sectors of the economies of countries around the world. As a result, the innovative development of tourism in the sectors of the economies of most countries around the world remains one of the most important tasks today.In different countries of the world, extensive scientific and practical research is being conducted to increase tourism potential, offer new services, create new tourism brands, radically increase the competitiveness of the tourism industry, conduct statistical research in the tourism industry and statistically assess the innovative development of tourism. The issues of statistical assessment of tourism have not been sufficiently addressed in the research. This makes it urgent to further expand the geography of tourism in research, increase its share in the economy of countries, in particular in the gross domestic product, and turn tourism into one of the profitable sectors.
Keywords: Tourism receipts, tourism consumption, tourism auxiliary account, tourism statistics, forecasting methods